The chemokine receptor CXCR7 influences prognosis in human glioma in an IDH1-dependent manner. Issue 10 (24th June 2015) - Birner, Peter; Tchorbanov, Andrey; Natchev, Sevdalin; Tuettenberg, Jochen; Guentchev, Marin
Abstract : Aims: The chemokine receptor CXCR7 is found on glioma cells and glioma-associated vessels and dependent upon its localisation on tumour or endothelial cells the CXCR7 receptor can mediate glioma cell invasion and tumour angiogenesis. Its expression predicts survival in several types of cancers. Methods: We immunohistochemically studied the expression of CXCR7 and its ligand SDF1α in a cohort of 354 human patients with glioma. In an in vivo glioma model, we studied the effect of selective CXCR7 inhibition on mean vascular density. Results: Here we show that expression of either mutant isocitrate dehydrogenase (IDH) 1 or podoplanin (PDPN), two proteins present in basically non-overlapping glioma populations, predicts the prognostic significance of CXCR7. Specifically, expression of CXCR7 on endothelial cells in IDH1 mutant cases predicted poor outcome. Surprisingly, in PDPN expressing gliomas, one of the marker genes for the recently identified mesenchymal subgroup, expression of CXCR7 predicts diminished prognosis on tumour cells and better prognosis on endothelial cells. Conclusions: Since CXCR7 is expressed on migrating cells our data suggest that, although ubiquitously present, angiogenesis and invasion are outcome-relevant events in specific glioma subgroups, providing a potentially important tool for targeted therapy assignment.